Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/hfm.10008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual lighting on visual performance and eye fatigue

Abstract: This study is designed to determine whether differences in eye fatigue and visual performance can be shown under varying virtual industrial lighting conditions. It is based on the results of studies of more traditional video display terminal (VDT) tasks reported in the literature. One experiment was designed to determine if the effects of virtual lighting on eye fatigue and visual performance in a simulated virtual industrial environment are similar to some other VDT tasks with varying luminance contrast. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…When people in workplace face inadequate level of light intensity, they try to make up this defect by pressuring on their eye muscles and continue to their activities and complete their tasks. This leads to eye tiredness and frequent headaches which can be a negative effective factor on sleep quality itself [12]. This defect can be fixed by improving the light intensity of the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When people in workplace face inadequate level of light intensity, they try to make up this defect by pressuring on their eye muscles and continue to their activities and complete their tasks. This leads to eye tiredness and frequent headaches which can be a negative effective factor on sleep quality itself [12]. This defect can be fixed by improving the light intensity of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study showed that the level of lighting affected practitioners' performance and their eye fatigue [12]. In a research on improving nurse performance with appropriate design of light, which was done by Kamalii and Abbas in 2011, it was found that with a appropriate lighting design, the performance of nurses was improved, and their fault rate was diminished [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the perceivable symptoms of visual fatigue are blurred vision, ocular pain, ocular swelling, headaches, and dry eyes [16]. Viewing distance [12], ambient lighting [17,18], display resolution [19], mental workload [20], glare [21,22], viewing angle [23,24], and length of continuous viewing time [6] all have been shown to increase visual fatigue with video display terminal use. Sanchez-Roman et al compared two groups of workers, one using computers and the other not [25] and found that 4 h at the computer was sufficient to produce asthenopia.…”
Section: Visual Fatiguementioning
confidence: 99%
“…All the participants had to determine the acceptability level for each initial experimental condition. The magnitude estimation was used to examine their perceived level of acceptability (Duffy & Chan, 2002). To make their scaling judgements consistent between subjects, the six steps transformation of modulus equalization proposed by Snow and Williges (1998) was applied to the data.…”
Section: Perceived Acceptabilitymentioning
confidence: 99%
“…The results have implications for both services and manufacturing industries (Duffy & Salvendy, 2000) where full and hybrid automation are an integral part of workplace design and where perception has safety implications (Duffy, Wu, & Ng, 2003) and performance implications (Duffy & Chan, 2002). Training can impact recognition of the hazardous conditions (Duffy, 2003;Duffy, Ng, & Ramakrishnan, 2004).…”
Section: Perception Of Safe Robot Speedmentioning
confidence: 99%